IMPLEMENTASI PENDIDIKAN KARAKTER DI MADRASAH - Amrullah, Abdul Malik Karim (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2012)
Character education is the systematical approach to develop and safe fitrah (natural values) for potencials of human being (human actualization). The implication of the systematical approach is how to make a good planning and teach a fitrah (a natural values) in order to became good values and for the final purposes in order tobe a good behavior. So education for character will be well apllied if every teacher has good values or character.